2021
DOI: 10.4236/ojbm.2021.91003
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Job Stress and Overall Compensation Benefits on Employees’ Job Satisfaction with Moderation Effect of Leadership: An Empirical Study in the Telecommunication Industry of Cameroon

Abstract: Background: Nowadays, existence of self-motivated and efficient human resource is a key issue of great importance in the telecommunication industry. Considering that human resource in an organization is significant resources, steps should be taken to find the strong and weak points in enhancing the operation of increasing efficiency in the firm. Moreover, job satisfaction has been considered one of the important factors in the provision of superior performance and high quality services at the telecommunication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 97 publications
0
8
0
2
Order By: Relevance
“…Remunerasi merupakan salah satu indikator untuk menjadikan pegawai puas (Tian et al, 2021). Pemberian remunerasi yang menarik dan memadai sesuai dengan preferensi, kebutuhan dan kinerja pegawai digunakan oleh organisasi untuk mempertahankan karyawan potensialnya (Peprah et al, 2017), dan remunerasi, pengembangan karir, leadership, work life balance merupakan keseluruhan indikator untuk mengukur kepuasan kerja karyawan (Stamolampros et al, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Remunerasi merupakan salah satu indikator untuk menjadikan pegawai puas (Tian et al, 2021). Pemberian remunerasi yang menarik dan memadai sesuai dengan preferensi, kebutuhan dan kinerja pegawai digunakan oleh organisasi untuk mempertahankan karyawan potensialnya (Peprah et al, 2017), dan remunerasi, pengembangan karir, leadership, work life balance merupakan keseluruhan indikator untuk mengukur kepuasan kerja karyawan (Stamolampros et al, 2019).…”
Section: Pendahuluanunclassified
“…Ditunjukkan dengan hasil pada pernyataan yang membahas tentang financial wellbeing, didominasi oleh luapan rasa percaya diri dari pegawai atas kondisi ini. Sejalan dengan penelitian yang dilakukan oleh Agustiningsih et al, (2016), Bernsten & Karolina (2010), Cahyonugroho et al (2016, dan Tian et al, (2021) bahwa remunerasi memberikan dampak psikologis kepada pegawai yaitu ada perasaan nyaman, tenang atas kondisi keuangan yang dimiliki.…”
Section: Tabel 3 Hasil Goodness Of Fit Modelunclassified
“…(Ivanov & Usheva, 2021) "Job performance is the amount of successful role achievement". According to (Tian et al, 2021) provides an understanding of performance as something that is done and produced in the form of products or services, within a certain period and a certain size by a person or group of people through their skills, abilities, knowledge and experience.…”
Section: Human Research Performancementioning
confidence: 99%
“…The work environment in a company is very important to pay attention to its comfort because the work environment is very important in carrying out all activities at work because every day employees are in a work environment if employees like the work environment then in terms of working they will feel safe and comfortable so they will feel at home and fun in doing everything to work more optimally and can use time effectively, whereas if the work environment is not comfortable it will reduce its activities so that work is less effective and can reduce employee performance. Some experts define the work environment as follows: According to (Tian et al, 2021) the work environment is everything that is around employees and can affect the performance of the tasks assigned to them, for example with the presence of air conditioner (AC), adequate lighting and so on. The work environment is something that exists in the workers' environment that can influence themselves in carrying out tasks such as temperature, humidity, ventilation, lighting, noise, cleanliness of the workplace and whether or not work equipment is adequate.…”
Section: Work Environmentmentioning
confidence: 99%
“…This lead to poor job commitment of some private teachers thereby constantly, increasing their intention to leave their job. Studies have shown that job satisfaction and commitment have a positive impact on organizational performance [5,6]. As such, the satisfaction and commitment of a teacher are considered a significant panacea for their performance [7].…”
Section: Introductionmentioning
confidence: 99%